The synthesis and characterisation of pyrochlore zirconates - Chiya, Thabang Jazyqueen (My University, 2017)
In this research project, the synthesis, chemistry and thermoresponsive behavior of pyrozirconates of the structure type A2Zr2O7 (A= La, Sm, Y) were investigated. The materials synthesized were coupled with doped analogues of the structure type AA’Zr2O7 where A and A’ were 1:1 mixture of La, Sm, Y. Investigating the structural dynamics and thermal behavior of the materials revealed high thermal stability of the materials while some of the doped analogues were unstable with increasing temperatures. The materials were synthesized using the sol-gel route and were all characterized using powder X-ray diffraction (PXRD) coupled with Rietveld refinement for structural refinement and solution. The thermoresponsive behavior was investigated using variable temperature PXRD along with Rietveld refinement for the measurement of thermal expansion coefficients. The doped analogues were also characterized using electron probe micro-analyzer (EPMA) for mapping studies. The mechanochemical synthesis route was also employed in the synthesis of La2Zr2O7 using a planetary ball mill. This material was also charaterised using PXRD both for structure determination and thermoresponsive studies. The ball mill consisted of a stainless steel jar and this had implications on the final product, this is an observation which has never been explored before. This dissertation consists of 6 chapters. Chapter 1 reviews the scientific literature of pyrochlore type structures, chapter 2 best describes the methods of synthesis and characterization of the mayterials. Chapter 3 was an investigation of pyrochlore zirconates of the structure type A2Zr2O7 (A= La, Sm, Y), their phase composition, structural determination and thermoresponsive behavior. Chapter 4 describes La2Zr2O7 as synthesized by the wet mechanochemical route; the method was efficient and gave products with a higher percentage yield while showing that the use of a stainless steel pot or balls in a planetary ball mill extracts Fe2O3 from the pot or balls. This led to the Fe2O3 reacting with La2O3 and leading to a perovskite structure type which was present in the final product. Chapter 5 was the investigation of LaSmZr2O7, LaYZr2O7 and SmYZr2O7. These were all synthesized using the sol-gel route and characterized using PXRD with Rietveld refinement for structural determination and thermoresponsive behavior studies. III LaSmZr2O7 and LaYZr2O7 were unstable at high temperature while SmYZr2O7 was the only material that possessed stability at high temperatures. The phase compositions of the materials were investigated using EPMA which gave a better overview of what single powder crystals of each of the materials contained. LaSmZr2O7 and LaYZr2O7 which were unstable; revealed that the A3+ cations were not evenly distributed on the crystals. SmYZr2O7 revealed and even distribution of Sm and Y throughout the crystals. This material was then investigated using variable temperature PXRD and the thermal expansion coefficient (TEC) was determined, this was a first report of the TEC of SmYZr2O7.
A dissertation submitted in fulfilment of the requirements for the degree Master of Science in Chemistry to the Faculty of Science, University of the Witwatersrand, Johannesburg. June 2017
Keywords: Metals--Thermal properties; Zirconates